Using faecal glucocorticoid metabolite analyses to elucidate stressors of African wild dogs Lycaon pictus from South Africa. Issue 1 (17th March 2020) - Crossey, Bruce; Chimimba, Christian; du Plessis, Cole; Hall, Grant; Ganswindt, Andre
Abstract : There are few stressful factors which have been investigated to affect adrenocortical function in the African wild dog (AWD) Lycaon pictus. Understanding what animals perceive as stressors is important for not only the implementation of management practices promoting general animal welfare in captivity, but also because a prolonged stress perception is known to disrupt reproduction, immune function and ultimately pose a threat to survival. In this regard, faecal glucocorticoid metabolite (fGCM) measurements are commonly used as a non‐invasive approach to assess the impact of factors which may be acting as perceived stressors in wildlife. This study was aimed at determining if there are significant differences in AWD fGCM concentrations as a result of sex, presence of absence of an injury, age‐class, body condition, dietary provisioning (through stable nitrogen (δ15N) and carbon (δ13C) isotope analysis), hierarchal status, and setting (i.e. captive or free‐ranging). A total of 47 faecal samples were collected immediately post‐defaecation from 39 AWDs across four free‐ranging sites (Hluhluwe‐iMfolozi Park, Madikwe Game Reserve, Kruger National Park and the Waterberg), two permanently captive sites (Johannesburg and Pretoria Zoo), and four temporary captive holding facilities (Hoedspruit Endangered Species Centre and Maremani, Tembe and Zimanga bomas) in South Africa. Captive AWDs had distinctively higher fGCM levels than their free‐ranging counterparts, regardless of sex, body condition, hierarchal status, age‐class or dietary provisioning. The present study is the first to assess physiological stress responses across permanently captive, temporarily captive and free‐ranging AWDs within the South African managed metapopulation, while incorporating the use of stable isotope analysis to quantify differences in dietary isotopic profiles between these different settings. Ultimately this demonstrates the usefulness of fGCM analysis as a tool for assessing animal welfare in both captive and free‐ranging AWDs, and underpins the importance of understanding factors perceived as stressors for the management of the species. Keywords: animal welfare, body condition scoring, faecal glucocorticoid metabolite monitoring, managed metapopulation, stress, wildlife management.